(untitled) (Tidsskrift for Praktisk Teologi, 2023)
Book review of Pete Ward and Knut Tveitereid (eds.). The Wiley Blackwell Companion to Theology and Qualitative Research, ed. by Pete Ward and Knut Tveitereid.